2007
DOI: 10.1002/ajmg.a.31620
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 6 (IRF6) and fibroblast growth factor receptor 1 (FGFR1) contribute to human tooth agenesis

Abstract: Phenotypic characteristics expressed in syndromes give clues to the factors involved in the cause of isolated forms of the same defects. We investigated two genes responsible for craniofacial syndromes, FGFR1 and IRF6, in a collection of families with isolated tooth agenesis. Cheek swab samples were obtained for DNA analysis from 116 case/parent trios. Probands had at least one developmentally missing tooth, excluding third molars. In addition, we studied 89 cases and 50 controls from Ohio to replicate any pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 32 publications
5
75
0
11
Order By: Relevance
“…Expression analysis of these tissues during development also supports an overlapping role [Vieira et al, 2007b]. Our study provides further evidence that common genetic factors may contribute to both CL/P and dental anomalies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Expression analysis of these tissues during development also supports an overlapping role [Vieira et al, 2007b]. Our study provides further evidence that common genetic factors may contribute to both CL/P and dental anomalies.…”
Section: Discussionsupporting
confidence: 73%
“…This region is relatively close to IRF6 (1q32.2). Our previous work found a strong association between IRF6 and clefts [Zucchero et al, 2004;Vieira et al, 2007a], and isolated tooth agenesis [Vieira et al, 2007b]. However, we were not able to identify the functional genetic variant yet.…”
Section: Discussionmentioning
confidence: 68%
“…FGFR1 (member of receptor tyrosine kinases) is expressed on both osteoclasts and osteoblasts, and influences osteogenic differentiation of stem cells (23)(24)(25). Its mutations and haplotypes are associated with skeletal deformities seen in Pfeiffer and Kallmann syndromes, human tooth agenesis (26), and normal variations in craniofacial shape (27). In a recent study, decreased expression of FGFR1 in osteoporotic bone tissue was demonstrated (13).…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, diş eksikliğine neden olan en önemli aday genlerden biri olarak belirtilmektedir. 3,13,35,57 "T-BOX TRANSCRIPTION FACTOR (TBX22)"…”
Section: "Interferon Regulatory Factor-6 (Irf6)"unclassified